Assessing the use and understanding of the Portuguese heat–health warning system (ÍCARO). (13th March 2020) - Leite, A; Santos, A J; Silva, S; Nunes, B; Mexia, R; Rodrigues, A P
ABSTRACT: Background: Heatwaves can lead to increased mortality. In the Portuguese heat–health warning system (HHWS), ÍCARO, a daily report with heat-related mortality prediction is sent to heat–health action plan (HHAP) practitioners. HHAP practitioners assess risk and implement measures to prevent heatwave-related impact, but ÍCARO's use and understanding are unknown. We assessed ÍCARO's use and understanding by key HHAP practitioners. Methods: We conducted semi-structured interviews with national/regional HHAP practitioners. Interviews were recorded, transcribed and analysed using thematic content analysis. To maximize credibility a validation process was implemented through researcher triangulation; a sample of 30 segments was recorded by independent researchers. Results: We conducted six interviews with nine professionals (mean time 52 min) from five regions. We identified four categories: report's content and presentation, report's reception and communication, ÍCARO and risk assessment and other issues. Practitioners use ÍCARO and perceived it as relevant; they raised issues on its interpretation and felt these were not fully addressed, given researchers' use of statistical/epidemiological terms. We identified the need for improved communication and report's clarity. Conclusions: Our study stresses the need for collaboration between experts within HHWS/HHAP. Despite ÍCARO's understanding being challenging, practitioners consider it a relevant tool. Researchers should use less statistical language and clarify ÍCARO's interpretation. Practitioners' needs should be considered when developing/revising tools.